A doped iridium oxide catalyst and its preparation method and application
By doping corrosion-resistant metals and acid-unstable metals in low-crystalline iridium oxide catalysts, the electronic structure of the catalyst is regulated, and the problems of high cost and poor stability of Ir-based catalysts are solved, and efficient and low-cost proton exchange membrane electrolysis hydrogen production technology is achieved.
Patent Information
- Application Number
- CN202410393813.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-04-02
AI Technical Summary
In the existing proton exchange membrane electrolytic hydrogen production technology, the high cost of Ir-based catalysts and the stability of low crystallinity IrOx catalysts limit the energy conversion efficiency and large-scale applications of hydrogen production.
By doping corrosion-resistant metals such as titanium, zirconium, hafnium, vanadium, niobium or tantalum in a low-crystalline iridium oxide catalyst, an Ir-O-M bridge interface is formed, the Ir and O electronic structure is regulated, and the acid-unstable metals are combined to reduce the crystallinity of the catalyst.
The high activity and stability of the catalyst are achieved, the amount of precious metal Ir is reduced, the energy conversion efficiency of hydrogen production by electrolyzing water in the proton exchange membrane is improved, and it is suitable for large-scale industrial production.
Smart Images

Figure HDA0004773359600000011 
Figure HDA0004773359600000012 
Figure HDA0004773359600000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and specifically relates to a doped iridium oxide catalyst and a preparation method and application thereof. Background Art
[0002] As we all know, the proton exchange membrane electrolysis of water (PEMWE) technology coupled with renewable energy is a key means to achieve zero-carbon emissions and green hydrogen production. The PEMWE process generally includes oxygen evolution reaction (OER) on the anode side and hydrogen evolution reaction (HER) on the cathode side. Among them, the HER side catalyst has high activity and good stability, while the OER side has slow kinetics and usually requires the use of a large amount of high-cost precious metal Ir-based catalysts, which has become the main bottleneck for the practical application of PEMWE technology. In addition, the intrinsic activity of traditional iridium oxide catalysts is low, resulting in low energy conversion efficiency of PEMWE hydrogen production, which is not conducive to its large-scale application. Therefore, improving the activity of Ir-based OER-side catalysts to improve the energy conversion efficiency of PEMWE hydrogen production has become the focus of many researchers.
[0003] Studies have shown that the electronic structure of the Ir site can be optimized by reducing the crystallinity of IrO2, and the resulting low-crystallinity IrOx catalyst can express high activity. x While the activity is improved, the operational stability of the catalyst decreases rapidly (i.e., deactivation), resulting in certain limitations on its practical application.
[0004] At present, in order to suppress the low crystallinity IrO x In order to reduce the stability of catalysts, some studies have proposed strategies to utilize the interaction between catalysts and carriers and to adjust the crystallinity of catalysts. For example, some studies have pointed out that the low crystallinity IrO x The catalyst is loaded onto the surface of a suitable carrier (Ti4O7, TiO2) and reacts with IrO x The electron transfer effect between catalysts inhibits the deep oxidation and dissolution of Ir under high oxidation potential conditions, thereby avoiding the formation of IrO x Catalyst deactivation. In addition, some studies have pointed out that for low crystallinity IrO x The catalyst is heat treated in an oxidizing atmosphere to transform it into IrO2 with relatively higher crystallinity, thereby reducing the defect content in the catalyst and inhibiting the loss of Ir in the active center under operating conditions.
[0005] However, the introduction of the carrier will, on the one hand, reduce the conductivity of the catalyst, making it difficult to express its performance in a PEMWE single cell; on the other hand, the interaction between the catalyst and the carrier only occurs at the interface between the two, with a small range of action, and the effect on improving the stability of the catalyst is limited. While improving the crystallinity, while improving the operational stability, it will inevitably lead to a decrease in the activity of the catalyst, so it is impossible to achieve a catalyst with both high activity and high stability. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a doped iridium oxide catalyst and a preparation method and application thereof. The doped iridium oxide catalyst has both high activity and high stability.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a doped iridium oxide catalyst, which comprises low-crystallinity iridium oxide and a corrosion-resistant metal doped in the low-crystallinity iridium oxide;
[0009] The corrosion-resistant metal is selected from any one or more of titanium, zirconium, hafnium, vanadium, niobium or tantalum.
[0010] It should be noted that the corrosion-resistant metal doped in the low-crystallinity iridium oxide is in-situ doped in the low-crystallinity iridium oxide, that is, the corrosion-resistant metal replaces part of the Ir sites in the low-crystallinity iridium oxide in-situ.
[0011] Preferably, the low-crystallinity iridium oxide has a crystallinity of 0.5-50%.
[0012] Preferably, the mass percentage of the corrosion-resistant metal to the doped iridium oxide catalyst is 1-20%.
[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned doped iridium oxide catalyst, comprising:
[0014] A noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate, and an acid-labile metal salt are mixed with a solvent and dried to obtain a precursor;
[0015] The precursor is calcined and acid-washed to obtain a doped iridium oxide catalyst.
[0016] Preferably, the noble metal Ir source includes any one or more of iridium chloride, chloroiridic acid, potassium chloroiridate, sodium chloroiridate, iridium acetate or iridium acetylacetonate.
[0017] Preferably, the corrosion-resistant metal salt includes any one or more of titanium salt, zirconium salt, hafnium salt, vanadium salt, niobium salt or tantalum salt.
[0018] Preferably, the alkali metal nitrate includes any one or more of lithium nitrate, sodium nitrate, potassium nitrate, rubidium nitrate or cesium nitrate.
[0019] Preferably, the acid-labile metal salt comprises any one or more of zinc salt, strontium salt, yttrium salt or nickel salt.
[0020] Preferably, the solvent is selected from any one or more of water, ethanol or isopropanol.
[0021] Preferably, the atomic ratio of the corrosion-resistant metal in the corrosion-resistant metal source to Ir in the noble metal Ir source is (0.01-0.2):1.
[0022] Preferably, the atomic ratio of the acid-labile metal in the acid-labile metal salt to Ir in the noble metal Ir source is (0.05-0.25):1.
[0023] Preferably, the mass ratio of Ir in the noble metal Ir source to alkali metal nitrate is 20 mg: (0.1-10) g.
[0024] Preferably, the mass volume ratio of Ir in the noble metal Ir source to the solvent is (1-200) mg:10 mL.
[0025] Preferably, the calcination atmosphere is air, oxygen, nitrogen, argon or carbon dioxide; the calcination temperature is 300-550°C, and the heating rate is 1-10°C min -1 , time is 0.5~24h.
[0026] Preferably, the pickling acid is any one or more of hydrochloric acid, sulfuric acid or nitric acid.
[0027] Preferably, the concentration of the acid solution is 0.5 to 5 mol L -1 .
[0028] Preferably, the pickling temperature is 30 to 80° C. and the time is 6 to 24 hours.
[0029] In a third aspect, the present invention provides a proton exchange membrane water electrolysis anode catalyst slurry, comprising an anode catalyst, a dispersant, a binder and a solvent;
[0030] The anode catalyst is the doped iridium oxide catalyst involved in the above technical solution.
[0031] Preferably, it is characterized in that, preferably, the binder is perfluorosulfonic acid resin.
[0032] Preferably, the solvent is selected from any one or more of water, isopropanol and ethanol.
[0033] Fourth aspect, the present invention provides a membrane electrode assembly, which includes an anode catalyst layer, a cathode catalyst layer, and a proton exchange membrane;
[0034] The anode catalyst layer includes the doped iridium oxide catalyst involved in the above technical solution.
[0035] Fifth aspect, the present invention provides a proton exchange membrane water electrolysis hydrogen production electrolyzer, which includes the doped iridium oxide catalyst involved in the above technical solution, the proton exchange membrane water electrolysis anode catalyst slurry involved in the above technical solution, or the membrane electrode assembly involved in the above technical solution.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0037] The present invention provides a doped iridium oxide catalyst, which includes low-crystallinity iridium oxide and a corrosion-resistant metal doped in the low-crystallinity iridium oxide; the corrosion-resistant metal is selected from any one or more of titanium, zirconium, hafnium, vanadium, niobium, or tantalum. In the process of preparing the doped iridium oxide catalyst of the present invention, by introducing a corrosion-resistant metal and an acid-labile metal into the precursor, the corrosion-resistant metal partially replaces the Ir sites during the formation of IrO x to form in-situ doping of the corrosion-resistant metal (denoted as "M"), constructing a large number of Ir-O-M bridge interfaces, which has the effect of regulating the electronic structures of Ir and O, and further improving the operating stability of the catalyst. In addition, the acid-labile metal is removed during the subsequent pickling process, creating abundant defect sites, which has the effect of reducing the crystallinity of iridium oxide (abbreviated as "IrO x ", where 1 < x < 2), that is, obtaining low-crystallinity iridium oxide, so as to effectively maintain the high activity of the catalyst. In the doped iridium oxide catalyst provided by the present invention, the corrosion-resistant metal can be uniformly dispersed in the IrO x structure, effectively inhibiting the activation of lattice oxygen in the catalyst under reaction conditions; compared with the existing commercial catalysts, this doped iridium oxide catalyst can reduce the consumption of precious metal Ir, improve the catalytic activity, and maintain the stability.
[0038] In addition, the preparation method of the doped iridium oxide catalyst provided by the present invention is simple, suitable for large-scale industrial production, and can be scaled up to kilogram-level preparation, laying a foundation for mass preparation of high-efficiency and low-cost proton exchange membrane electrolysis water anode catalysts.
[0039] After testing, for the PEMWE single cell prepared by using the doped iridium oxide catalyst provided by the present invention as the anode catalyst, it is expected to still maintain 90% of its performance after operating at a current density of 3 A cm -2 for 20,000 h. Description of the Drawings
[0040] Figure 1The corrosion-resistant metal Ti-doped low-crystallinity IrO prepared in Example 1 of the present invention x The results of the constant potential stability test of the anode catalyst of the proton exchange membrane water electrolysis in 0.5M H2SO4 electrolyte;
[0041] Figure 2 The corrosion-resistant metal Zr-doped low-crystallinity IrO prepared in Example 2 of the present invention x XRD pattern of anode catalyst of proton exchange membrane water electrolysis;
[0042] Figure 3 The corrosion-resistant metal Hf-doped low-crystallinity IrO prepared in Example 3 of the present invention x Element mapping image of anode catalyst for proton exchange membrane water electrolysis;
[0043] Figure 4 The corrosion-resistant metal Hf-doped low-crystallinity IrO prepared in Example 4 of the present invention x O1s XPS spectrum of the anode catalyst of proton exchange membrane water electrolysis;
[0044] Figure 5 The low-crystallinity IrO doped with the corrosion-resistant metal Hf prepared in Example 5 of the present invention x Polarization curve of PEMWE single cell assembled with anode catalyst of proton exchange membrane water electrolysis;
[0045] Figure 6 The low-crystallinity IrO doped with the corrosion-resistant metal Hf prepared in Example 5 of the present invention x The constant current stability test results of the PEMWE single cell assembled with the anode catalyst of the proton exchange membrane water electrolysis;
[0046] Figure 7 The low-crystallinity IrO doped with the corrosion-resistant metal Hf prepared in Example 6 of the present invention x The constant current stability test results of the PEMWE single cell assembled with the anode catalyst of the proton exchange membrane water electrolysis;
[0047] Figure 8 The corrosion-resistant metal Nb-doped low-crystallinity IrO prepared in Example 7 of the present invention x The constant current stability test results of the PEMWE single cell assembled with the anode catalyst of the proton exchange membrane water electrolysis;
[0048] Fig. 9 The Co-doped low-crystallinity IrO prepared in Comparative Example 1 x The constant current stability test results of the PEMWE single cell assembled with the anode catalyst of proton exchange membrane water electrolysis. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] In the prior art, low crystallinity IrO x Catalysts cannot have both high stability and high activity at the same time. The present invention provides a doped iridium oxide catalyst, which includes low-crystallinity iridium oxide and a corrosion-resistant metal doped in the low-crystallinity iridium oxide.
[0051] In the present invention, the low crystallinity iridium oxide is a concept relative to the high crystallinity iridium oxide, specifically referring to the fact that the IrO6 octahedral structural unit in the prepared sample is not completely ordered and has a large number of defect sites. Through XRD analysis, it can be found that the crystallinity of the low crystallinity iridium oxide in the prepared doped iridium oxide catalyst is between 0.5 and 50%.
[0052] In the present invention, the corrosion-resistant metal can be specifically selected from any one or more of titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb) or tantalum (Ta), preferably any one or more of Hf, Nb and Ta.
[0053] In the present invention, the mass percentage of the corrosion-resistant metal in the doped iridium oxide catalyst is 1 to 20%, more preferably 5 to 10%, which ensures that the doped corrosion-resistant metal can be evenly dispersed in the IrO x On the one hand, it maximizes the density of the Ir-OM structure.
[0054] The present invention introduces a corrosion-resistant metal into iridium oxide, and the corrosion-resistant metal can replace part of the Ir sites in iridium oxide in situ, forming an in-situ doping of the corrosion-resistant metal (denoted as "M"), constructing a large number of Ir-OM bridge bond interfaces, playing an effect of regulating the electronic structure of Ir and O, and thus improving the operating stability of the doped iridium oxide catalyst. In addition, low-crystallinity iridium oxide can effectively maintain the high activity of the catalyst.
[0055] The present invention also provides a method for preparing the above-mentioned doped iridium oxide catalyst, comprising:
[0056] A noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate, and an acid-labile metal salt are mixed with a solvent and dried to obtain a precursor;
[0057] The precursor is calcined and acid-washed to obtain a doped iridium oxide catalyst.
[0058] According to the present invention, firstly, a noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate and an acid-unstable metal salt are mixed with a solvent and dried to obtain a precursor. In some embodiments of the present invention, it is preferred to mix a noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate and an acid-unstable metal salt with a solvent, and the mixing is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 0.2 to 4 hours, and more preferably 0.5 to 2 hours. Then, the obtained mixture is dried, and the drying is preferably rotary evaporation or stirring evaporation, and the drying temperature is 50 to 85°C, preferably 55 to 70°C. The drying time is not particularly limited, and is based on complete drying. After the drying is completed, a precursor is obtained.
[0059] In the present invention, the noble metal Ir source includes any one or more of iridium chloride, chloroiridic acid, potassium chloroiridate, sodium chloroiridate, iridium acetate or iridium acetylacetonate, preferably any one or more of iridium trichloride, potassium chloroiridate or chloroiridic acid; the corrosion-resistant metal salt includes titanium salt (such as titanium sulfate, titanyl sulfate, titanium acetylacetonate, titanium acetylacetonate oxide, potassium titanium oxalate, potassium bis(oxalate)oxytitanate, etc.), zirconium salt (such as zirconium nitrate, zirconyl nitrate, zirconium chloride, zirconyl chloride, zirconyl acetylacetonate, zirconyl acetylacetonate oxide, etc.), hafnium salt (such as hafnium chloride, hafnium oxynitrate, hafnium sulfate, hafnium acetylacetonate, etc.), vanadium salt (such as sodium vanadate, sodium metavanadate, vanadium acetylacetonate oxide, etc.), niobium salt The invention relates to any one or more of an alkali metal nitrate (such as ammonium niobate oxalate, niobium oxalate) or a tantalum salt (such as potassium fluorotantalate), preferably any one or more of a hafnium salt, a niobium salt or a tantalum salt; the alkali metal nitrate comprises any one or more of lithium nitrate, sodium nitrate, potassium nitrate, rubidium nitrate or cesium nitrate, preferably sodium nitrate and / or lithium nitrate; the acid-labile metal salt comprises any one or more of a zinc salt (such as zinc nitrate, zinc chloride), a strontium salt (strontium nitrate, strontium chloride), a yttrium salt (yttrium chloride, yttrium nitrate) or a nickel salt (nickel nitrate, nickel chloride), preferably a zinc salt and / or a yttrium salt; the solvent is selected from any one or more of water, ethanol or isopropanol, preferably water and / or isopropanol.
[0060] In the present invention, if the content of the corrosion-resistant metal in the doped iridium oxide catalyst is too high, a non-conductive corrosion-resistant metal oxide phase will be formed, and if it is too low, the density of Ir-OM will not be high enough. Therefore, the present invention preferably controls the atomic ratio of the corrosion-resistant metal in the corrosion-resistant metal source to the Ir in the noble metal Ir source to be (0.01-0.2):1, more preferably (0.05-0.10):1.
[0061] In the present invention, if the content of the added acid-labile metal is too high during the preparation of the doped iridium oxide catalyst, the structure of the iridium oxide will be completely destroyed, and if it is too low, sufficient defect sites cannot be formed. Therefore, the present invention preferably controls the atomic ratio of the acid-labile metal in the acid-labile metal salt to the Ir in the noble metal Ir source to be (0.05-0.25):1, more preferably (0.1-0.2):1.
[0062] In the present invention, the alkali metal nitrate is used to provide an oxidizing atmosphere to oxidize the Ir in the noble metal Ir source to IrO x If the amount of alkali metal nitrate is too high, it will be difficult to remove it later, and if it is too low, the precursor will not be completely converted into IrO. x Therefore, the present invention preferably controls the mass ratio of Ir to alkali metal nitrate in the noble metal Ir source to be 20 mg: (0.1 to 10) g, and more preferably 20 mg: (1 to 5) g.
[0063] In the present invention, the solvent provides a liquid environment. The present invention preferably controls the mass volume ratio of Ir in the noble metal Ir source to the solvent to (1-200) mg:10 mL, more preferably to (10-100) mg:10 mL.
[0064] According to the present invention, after obtaining the precursor, the precursor is calcined to convert the Ir source into active IrO in the presence of an alkali metal nitrate. x In some embodiments of the present invention, the dried precursor is preferably transferred to a muffle furnace for calcination, and the calcination atmosphere is preferably air, oxygen, nitrogen, argon or carbon dioxide. The calcination temperature is 300-550°C, preferably 350-450°C, and the calcination heating rate is 1-10°C min -1 , preferably 2~6℃min -1 , the time is 0.5 to 24 hours, preferably 1 to 12 hours.
[0065] After the calcination is completed, the obtained product is preferably cooled to room temperature and then acid washed to remove the acid-labile metals, thereby forming a x Create abundant defect sites on the surface to reduce IrO x In some embodiments of the present invention, the pickling acid is any one or more of hydrochloric acid, sulfuric acid or nitric acid, and the concentration of the acid is 0.5 to 5 mol L -1 , preferably 1 to 3 mol L -1 The pickling temperature is 30 to 80°C, preferably 40 to 60°C, and the time is 6 to 24 hours, preferably 12 to 18 hours.
[0066] In some preferred embodiments of the present invention, after the acid washing is completed, it is preferably filtered, washed and dried to obtain a doped iridium oxide catalyst. The washing reagent can be deionized water, and the number of washings is 1 to 3 times. The drying is vacuum drying or forced air drying at a temperature of 50 to 80° C., preferably 60 to 70° C., for 6 to 24 hours, preferably 8 to 12 hours.
[0067] The preparation method of the doped iridium oxide catalyst provided by the present invention is simple, suitable for industrial large-scale production, and can be scaled up to kilogram-level preparation, laying a foundation for the large-scale preparation of high-efficiency, low-cost proton exchange membrane water electrolysis anode catalysts. The method introduces corrosion-resistant metals and acid-labile metal components into the precursor, and prepares IrO x In the process, the corrosion-resistant metal partially replaces Ir to form corrosion-resistant metal-doped IrO x , by inhibiting the activation of lattice oxygen during the catalytic reaction to avoid the formation of amorphous IrO x The structure of the catalyst is destroyed, and the acid-labile metals are removed through the subsequent pickling treatment, which increases the amorphous degree of the catalyst and maintains the high activity of the catalyst.
[0068] XRD results show that the doped iridium oxide catalyst prepared by this method has the characteristics of low crystallinity; element mapping results show that the corrosion-resistant metal can be uniformly doped into IrO x The O 1s XPS data show that the introduction of corrosion-resistant metals can inhibit the activation of lattice oxygen, thereby preventing it from participating in the OER reaction, so that the doped iridium oxide catalyst maintains good operating stability. Stability tests were carried out in three-electrode and PEMWE single cells, and the results showed that the doped iridium oxide catalyst prepared by the present invention can maintain excellent catalytic activity for a long time.
[0069] The present invention also provides a proton exchange membrane water electrolysis anode catalyst slurry, comprising an anode catalyst, a dispersant, a binder and a solvent. The anode catalyst is the doped iridium oxide catalyst involved in the above technical solution; the binder is a perfluorosulfonic acid resin; and the solvent is selected from any one or more of water, isopropanol or ethanol.
[0070] The present invention also provides a membrane electrode assembly, which includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane. The anode catalyst layer includes the doped iridium oxide catalyst involved in the above technical solution. The cathode catalyst layer and the proton exchange membrane can be arranged according to the contents well known to those skilled in the art. For example, the cathode catalyst layer can be a commercial Pt / C catalyst, and the proton exchange membrane can be Nafion 115.
[0071] Based on the above content, the present invention also provides a proton exchange membrane water electrolysis hydrogen production electrolytic cell, which includes the doped iridium oxide catalyst involved in the above technical solution, the proton exchange membrane water electrolysis anode catalyst slurry involved in the above technical solution or the membrane electrode assembly involved in the above technical solution.
[0072] At present, in the prior art, the performance of a single cell for hydrogen production by proton exchange membrane electrolysis of water has a significant attenuation after running for about 200 hours. However, the PEMWE single cell prepared by using the iridium oxide-doped catalyst as the anode catalyst provided by the present invention generally has a high performance at 3A cm -2 It is expected that 90% of the performance will be maintained after running for 20,000 hours at the current density.
[0073] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.
[0074] Example 1
[0075] Weigh 8.7 mg of potassium titanium oxalate, 10 mg of zinc nitrate hexahydrate, and 1.5 g of sodium nitrate and disperse them in 10 mL of deionized water. Add 1.3 mL of 17.5 mg Ir mL -1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 5℃min -1 The temperature was raised to 350 °C at a rate of 1 h, maintained for 1 h, and cooled naturally to room temperature; the product was acid-washed with 50 mL 2.5 M HCl at room temperature for 12 h, filtered, washed with deionized water for multiple times, and dried in a vacuum at 50 °C for 6 h to obtain corrosion-resistant Ti-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0076] The corrosion-resistant Ti-doped low-crystallinity IrO prepared in Example 1 was subjected to electrochemical treatment in a 0.5 M H2SO4 electrolyte. x The OER catalytic stability test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis was carried out. The results are shown in the attached Figure 1 As shown, the corrosion resistant Ti-doped low crystallinity IrO x The performance decay rate of the sample was reduced by 11.3% compared with the undoped sample after stable operation at a potential of 1.6 V for 5 h, indicating that the corrosion-resistant Ti doping can effectively improve the performance of low-crystallinity IrO x Operational stability of the catalyst.
[0077] Example 2
[0078] Weigh 5.7 mg zirconium oxynitrate, 10 mg zinc nitrate hexahydrate, and 3 g sodium nitrate and disperse them in 10 mL deionized water. Add 1.5 mL 17.5 mg Ir mL-1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 5℃ min -1 The temperature was raised to 350°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL of 0.5 M H2SO4 at 50°C for 24 h, filtered, washed with deionized water for several times, and dried at 60°C for 4 h to obtain corrosion-resistant Zr-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0079] The corrosion-resistant Zr-doped low-crystallinity IrO prepared in Example 2 x The XRD test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water is shown in the following results: Figure 2 As shown, it can be clearly observed that no new diffraction peaks are generated in the XRD spectrum of the corrosion-resistant Zr-doped sample, indicating that Zr doping does not produce phase separation.
[0080] Example 3
[0081] Weigh 7.8 mg of hafnium chloride, 20 mg of zinc nitrate hexahydrate, and 3 g of sodium nitrate and disperse them in a mixed solvent of 10 mL of deionized water and 5 mL of ethanol, add 60 mg of IrCl3, and disperse them by ultrasonic for 0.5 h; rotary evaporate the precursor, place it in a muffle furnace, and heat it at 5 °C min -1 The temperature was raised to 350°C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL 0.5 M H2SO4 at 50°C for 24 h, filtered, washed with deionized water for several times, and dried at 65°C for 3 h to obtain corrosion-resistant Hf-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0082] The corrosion-resistant Hf-doped low-crystallinity IrO prepared in Example 3 x The element mapping test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water was carried out. The results are shown in the attached Figure 3 As shown, the corrosion resistant Hf element in IrO x Uniformly dispersed in the anode catalyst for hydrogen production by proton exchange membrane water electrolysis.
[0083] Example 4
[0084] Weigh 7.8 mg of hafnium chloride, 20 mg of yttrium nitrate hexahydrate, and 3 g of sodium nitrate and disperse them in a mixed solvent of 10 mL of deionized water and 5 mL of isopropanol. Add 60 mg of IrCl3 and disperse them by ultrasonic for 0.5 h. Rotary evaporate the precursor and place it in a muffle furnace at 5 °C min -1The temperature was raised to 350 °C at a rate of 100 °C, maintained for 0.5 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL 1 M HNO3 at room temperature for 6 h, filtered, washed with deionized water for several times, and dried under vacuum at 50 °C for 8 h to obtain corrosion-resistant Hf-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0085] The corrosion-resistant Hf-doped low-crystallinity IrO prepared in Example 4 x XPS test of the anode catalyst for hydrogen production by proton exchange membrane electrolysis of water. The results are shown in the attached Figure 4 As shown in the figure, after Hf doping, the oxygen vacancy content in the sample is significantly reduced, indicating that the introduction of Hf can effectively avoid the formation of lattice oxygen vacancies, thereby improving the operating stability of the catalyst.
[0086] Example 5
[0087] Weigh 14 mg of hafnium chloride, 20 mg of zinc nitrate hexahydrate, and 0.5 g of sodium nitrate and disperse them in a mixed solvent of 10 mL of deionized water and 5 mL of ethanol. Add 1 mL of 35 mg Ir mL -1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 2℃ min -1 The temperature was raised to 350°C at a rate of 100 °C, maintained for 2 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL of 1 M HCl at 50°C for 24 h, filtered, washed with deionized water for several times, and dried at 60°C for 4 h to obtain corrosion-resistant Hf-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0088] The corrosion-resistant Hf-doped low-crystallinity IrO prepared in Example 5 x The anode catalyst of proton exchange membrane water electrolysis was used as the anode, and a PEMWE single cell was assembled to conduct polarization curve test. The results are shown in the attached figure. Figure 5 As shown in the figure, the two curves correspond to different catalyst loadings (i.e. different precious metal Ir loadings) in the PEMWE single cell, and one curve corresponds to an Ir loading of 56 μg cm -2 The other curve corresponds to a loading of 330 μg cm -2 , indicating that corrosion resistant Hf-doped low-crystallinity IrO x The anode catalyst for proton exchange membrane water electrolysis to produce hydrogen has excellent catalytic performance, and even in a single cell with low catalyst loading, the catalyst still has high activity and can express excellent performance.
[0089] The corrosion-resistant Hf-doped low-crystallinity IrO prepared in Example 5 xThe anode catalyst of proton exchange membrane water electrolysis is the anode, Nafion115 is the proton exchange membrane, and 40wt% Pt / C is the cathode catalyst. The PEMWE single cell is assembled at 1.5A cm -2 The stability test was carried out under the current density, and the results are shown in the attached Figure 6 As shown in Figure 2, the performance decay rate is only 13 μV h after running for 1500 h. -1 , indicating that the corrosion-resistant Hf-doped low-crystallinity IrOx proton exchange membrane water electrolysis hydrogen production anode catalyst has excellent operating stability.
[0090] Example 6
[0091] Weigh 14 mg of hafnium chloride, 20 mg of zinc nitrate hexahydrate, and 2 g of lithium nitrate and disperse them in a mixed solvent of 10 mL of deionized water and 5 mL of ethanol. Add 1 mL of 35 mg Ir mL -1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 2℃ min -1 The temperature was raised to 400°C at a rate of 100 °C, maintained for 2 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL of 1 M HCl at 50°C for 24 h, filtered, washed with deionized water for several times, and dried at 60°C for 6 h to obtain corrosion-resistant Hf-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0092] The corrosion-resistant Hf-doped low-crystallinity IrO prepared in Example 6 x The anode catalyst of proton exchange membrane water electrolysis was used as the anode to assemble the PEMWE single cell. -2 The stability test was carried out under the current density, and the results are shown in the attached Figure 7 As shown in Figure 2, the performance decay rate is only 9.5 μV h after running for 2000 h. -1 , indicating that corrosion resistant Hf-doped low-crystallinity IrO x The anode catalyst for hydrogen production by proton exchange membrane water electrolysis has excellent operating stability.
[0093] Example 7
[0094] Weigh 7 mg of ammonium niobate oxalate, 30 mg of lanthanum nitrate hexahydrate, and 3 g of sodium nitrate and disperse them in 20 mL of deionized water. Add 1.2 mL of 35 mg Ir mL -1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 2℃ min -1The temperature was raised to 450°C at a rate of 100 °C, maintained for 2 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL of 1 M HCl at 50°C for 24 h, filtered, washed with deionized water for several times, and dried at 50°C for 6 h to obtain corrosion-resistant Nb-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0095] The corrosion-resistant Nb-doped low-crystallinity IrO prepared in Example 7 x The anode catalyst of proton exchange membrane water electrolysis was used as the anode to assemble the PEMWE single cell. -2 The stability test was carried out under the current density, and the results are shown in the attached Figure 8 As shown in Figure 2, there is no performance degradation after 250 h of operation, indicating that the corrosion-resistant Nb-doped low-crystallinity IrO x The anode catalyst for hydrogen production by proton exchange membrane water electrolysis has excellent operating stability.
[0096] Comparative Example 1
[0097] Weigh 20 mg of cobalt nitrate hexahydrate, 20 mg of zinc nitrate hexahydrate, and 3 g of sodium nitrate and disperse them in 20 mL of deionized water. Add 2 mL of 35 mg Ir mL -1 H2IrCl6, ultrasonic dispersion for 0.5h; rotary evaporation to obtain the precursor, placed in a muffle furnace, at 2℃ min -1 The temperature was raised to 400 °C at a rate of 100 °C, maintained for 2 h, and cooled naturally to room temperature. The product was acid-washed with 50 mL of 1 M HCl at 50 °C for 24 h, filtered, washed with deionized water for several times, and dried under vacuum at 60 °C for 4 h to obtain Co-doped low-crystalline IrO x Anode catalyst for hydrogen production by proton exchange membrane electrolysis of water.
[0098] The Co-doped low-crystallinity IrO x The anode catalyst of proton exchange membrane water electrolysis was used as the anode to assemble the PEMWE single cell. -2 The stability test was carried out under the current density, and the results are shown in the attached Fig. 9 As shown in the figure, the performance decayed significantly after 25 h of operation. This is because although Co has a certain acid resistance, it is still easy to dissolve under oxidative acidic conditions. On the one hand, it destroys the original catalyst structure and inactivates it. On the other hand, the dissolved Co ions may migrate to the proton exchange membrane, causing the single cell performance to drop sharply.
[0099] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A doped iridium oxide catalyst, characterized in that: The invention comprises low-crystallinity iridium oxide and a corrosion-resistant metal doped in the low-crystallinity iridium oxide; The corrosion-resistant metal is selected from any one or more of titanium, zirconium, hafnium, vanadium, niobium or tantalum; The low-crystallinity iridium oxide has a crystallinity of 0.5-50%; The preparation method of the doped iridium oxide catalyst comprises: A noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate, and an acid-labile metal salt are mixed with a solvent and dried to obtain a precursor; The precursor is calcined and acid-washed to obtain a doped iridium oxide catalyst.
2. The doped iridium oxide catalyst according to claim 1, characterized in that The mass percentage of the corrosion-resistant metal to the doped iridium oxide catalyst is 1-20%.
3. A method for preparing a doped iridium oxide catalyst as claimed in claim 1 or 2, characterized in that: include: A noble metal Ir source, a corrosion-resistant metal source, an alkali metal nitrate, and an acid-labile metal salt are mixed with a solvent and dried to obtain a precursor; The precursor is calcined and acid-washed to obtain a doped iridium oxide catalyst.
4. The preparation method according to claim 3, characterized in that: The noble metal Ir source includes any one or more of iridium chloride, chloroiridic acid, potassium chloroiridate, sodium chloroiridate, iridium acetate or iridium acetylacetonate; The corrosion-resistant metal source includes any one or more of titanium salt, zirconium salt, hafnium salt, vanadium salt, niobium salt or tantalum salt; The alkali metal nitrate includes any one or more of lithium nitrate, sodium nitrate, potassium nitrate, rubidium nitrate or cesium nitrate; The acid-labile metal salt includes any one or more of zinc salt, strontium salt, yttrium salt or nickel salt; The solvent is selected from any one or more of water, ethanol or isopropanol.
5. The preparation method according to claim 3, characterized in that: The atomic ratio of the corrosion-resistant metal in the corrosion-resistant metal source to the Ir in the noble metal Ir source is (0.01-0.2):1; The atomic ratio of the acid-labile metal in the acid-labile metal salt to the Ir in the noble metal Ir source is (0.05-0.25):1; The mass ratio of Ir to alkali metal nitrate in the noble metal Ir source is 20 mg:(0.1-10) g; The mass volume ratio of Ir in the noble metal Ir source to the solvent is (1-200) mg:10 mL.
6. The preparation method according to claim 3, characterized in that: The calcination atmosphere is air, oxygen, nitrogen, argon or carbon dioxide; the calcination temperature is 300-550°C, and the heating rate is 1-10°C min -1 , time is 0.5~24h; The pickling acid is any one or more of hydrochloric acid, sulfuric acid or nitric acid; The concentration of the acid solution is 0.5-5 mol L -1 ; The pickling temperature is 30~80°C and the time is 6~24 hours.
7. A proton exchange membrane water electrolysis anode catalyst slurry, characterized in that: including an anode catalyst, a binder and a solvent; The anode catalyst is the doped iridium oxide catalyst according to claim 1 or 2, or the doped iridium oxide catalyst prepared by the preparation method according to any one of claims 3 to 6.
8. The anode catalyst slurry for proton exchange membrane water electrolysis according to claim 7, characterized in that: The binder is selected from perfluorosulfonic acid resin; The solvent is selected from any one or more of water, isopropanol and ethanol.
9. A membrane electrode assembly, characterized in that: It includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane; The anode catalyst layer comprises the doped iridium oxide catalyst according to claim 1 or 2 or the doped iridium oxide catalyst prepared by the preparation method according to any one of claims 3 to 6.
10. A proton exchange membrane water electrolysis hydrogen production electrolytic cell, characterized in that: It comprises the doped iridium oxide catalyst according to claim 1 or 2, the doped iridium oxide catalyst prepared by the preparation method according to any one of claims 3 to 6, the proton exchange membrane water electrolysis anode catalyst slurry according to claim 7 or 8, or the membrane electrode assembly according to claim 9.
Citation Information
Patent Citations
Preparation method and device for metal oxide supported iridium / ruthenium-based catalyst
WO2022188278A1
Transition metal-doped iridium-based composite catalyst, and preparation and application thereof
WO2023208026A1